Building quality culture at vietnamese private universities (SciComm Report, 2021)
Quality Culture has a decisive role in maintaining and improving the quality of Vietnamese private universities to best meet the demand of customers. However, there is no private universities in Vietnam that has built quality culture based on a feasible and practical study. Therefore, this study is first implemented in Vietnam to address that situation of private universities. Based on theoretical and practical study, this study aims to give six solutions for building of Quality Culture to improve the quality of training and education, scientific research and public service of Vietnamese private universities.
Keywords: Vietnam; higher education; private universities; quality culture